Islamisasi ilmu sebagai respons terhadap tantangan globalisasi digital: Dinamika pemahaman keagamaan dalam era media sosial - Maltufah, Masnor; Rosyida, Nur Ayisya; Zuhroh, Nimatuz; Padil, Moh (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study aims to analyze the concept of Islamization of knowledge as a response to the challenges of digital globalization and to identify efforts to maintain alignment with Islamic values. This research employs a qualitative approach using a library research method by examining relevant academic literature. The results indicate that digital globalization facilitates access to religious information but also creates epistemological problems, such as the spread of unverified information, the decline of scholarly authority, and the tendency toward instant and partial religious understanding. In this context, the Islamization of knowledge becomes relevant as an effort to restore the orientation of knowledge to the principle of tawhid by integrating revelation, reason, and experience, as well as emphasizing the importance of adab (ethics) in seeking knowledge. The proposed efforts include strengthening digital literacy based on Islamic values (tabayyun), integrating knowledge with Islamic principles, and developing a critical attitude toward information. Thus, the Islamization of knowledge can serve as a framework for addressing digital globalization in a selective and responsible manner. Abstrak Penelitian ini bertujuan menganalisis konsep islamisasi ilmu sebagai respons terhadap tantangan globalisasi digital serta upaya menjaga keselarasan dengan nilai-nilai keislaman. Metode yang digunakan adalah pendekatan kualitatif dengan studi pustaka melalui kajian berbagai literatur ilmiah. Hasil penelitian menunjukkan bahwa globalisasi digital mempermudah akses informasi keagamaan, namun juga menimbulkan problem epistemologis seperti maraknya informasi tanpa validitas, menurunnya otoritas keilmuan, serta kecenderungan pemahaman agama yang instan dan parsial. Dalam konteks ini, islamisasi ilmu menjadi relevan sebagai upaya mengembalikan orientasi ilmu kepada nilai tauhid dengan mengintegrasikan wahyu, akal, dan pengalaman, serta menekankan pentingnya adab dalam berilmu. Adapun upaya yang dapat dilakukan meliputi penguatan literasi digital berbasis nilai keislaman (tabayyun), integrasi ilmu dengan nilai Islam, serta pengembangan sikap kritis terhadap informasi. Dengan demikian, islamisasi ilmu dapat menjadi kerangka dalam menghadapi arus globalisasi digital secara selektif dan bertanggung jawab.